Konservasi Penyu Melalui Pelepasan Tukik di Pantai Wisata Desa Maitara Kota Tidore Kepulauan - Taufiq Abdullah; Tamrin, Tamrin (Bakti Hayati: Jurnal Pengabdian Indonesia, 2024)
Sea turtles are one of the species essential for maintaining the balance of marine ecosystems, yet their populations have declined due to hunting, habitat destruction, and climate change. Sea turtle conservation is a crucial step in ensuring the sustainability of this species. This article discusses a community service activity involving the release of hatchlings as part of sea turtle conservation efforts at Maitara Village Tourism Beach, Tidore Islands City. The activity began with coordination among the village government, community leaders, and youth groups to plan and strategize implementation, involving all elements of the community. The release of hatchlings engaged students, tourists, and local residents, aiming to raise awareness and participation in sea turtle conservation. This activity not only provided hatchlings the opportunity to return to their natural habitat but also served as an educational platform to enhance public understanding of the importance of protecting sea turtles. Through a community-based approach, the program successfully strengthened collective commitment to coastal ecosystem conservation and opened opportunities for further development in support of natural resource conservation. The results of this activity demonstrate that collaboration among the community, academics, and government can have a significant positive impact on sea turtle conservation efforts.